A review of cold-formed steel built-up columns research at Curtin University - Lau, Hieng Ho; Ting, T. (CURTIN UNIVERSITY SARAWAK MALAYSIA, 2012)
Cold-formed steel construction has grown from a simple imitation of wood construction to an increasingly versatile construction system. Notable cold-formed steel innovations include built-up sections, custom-curved members, light weight steel hybrid, and wall framing. The amount of innovation in the products and related accessories for cold-formed steel has grown at an exponential rate during the last decade. However, only a handful of universities include cold-formed steel design in their undergraduate syllabus, although cold-formed steel is a good design material that is durable and green for sustainable construction practices nowadays. This paper summarises some of the cold-formed steel research carried out at Curtin University Sarawak Malaysia over the last five years especially in cold-formed steel built-up section.